PELATIHAN MEMBUAT AKSESORIS DARI LIMBAH KAIN PERCA (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2019)
The waste problems in Indonesia are very high. As many as 2% of the total waste in Indonesia comes from the fabric. The fabric waste can be processed into products with high economic value . A variety products from fabrics waste processing are bags, blankets, slippers, placemats table, as well as doormats are able to compete with big industries products. This research propose in processing fabric waste into a soundproof room partition. Room partition available now is indicated able to separate room visually, but not soundproofing between room. This study aim is to get a processed fabric whic is effective in decreasing the noise with the experimental method.The tests is carried out using multiple samples with each sample are given some degree of sound (125 Hz to 2000 Hz). The variety in sample is of material from denim patchwork and cotton patchwork. The benefits of this research is a room partition design that meets the beauty aspect of room decoration and the acoustic aspect in residential scope. The results of this research are processed patchwork stocky which are effective to reduce noise and provide a unique decorative motif.